Factors Affecting Consumptive Behavior of Management Study Program Students, Faculty of Economics and Business, Al-Qur'an University of Science, Class of 2021 - Savira, Vani; Yunaena, Ismi; Eriansyah; Efendi, Bachtiar (UM Purwokerto Press, 2025)
This study aims to determine the use of shopeepaylater, lifestyle, and financial literacy on the consumptive behavior of students in the Management Study Program, Faculty of Economics and Business, Al-Qur'an University of Science, Class of 2021. The lifestyle of today's students mostly imitates the style of someone seen through social media and always follows the existing trends. Lack of financial literacy can also be one of the causes of students to behave consumptively. For students who use the Shopeepaylater feature, financial literacy is needed because if using Shopeepaylater unwisely can cause students to be trapped in ongoing debt. Interest and additional fees from late payments will increase their financial burden. This study uses a quantitative approach with multiple linear analysis methods. The population in this study were FEB students of Al-Qur'an University of Science, Class of 2021. The research sample used purposive sampling technique with a total of 60 people. The data collection technique used in this study was a questionnaire. The instrument used in this research is a questionnaire. The data analysis technique used in this research is descriptive analysis. The results of this study indicate that use of shopeepaylater, financial literacy and lifestyle variables have a positive affect consumptive behavior.The implications of this study are to emphasize the importance of understanding financial literacy and a good lifestyle as a strategy to direct students in using the shoppepaylater feature wisely so as not to be trapped in consumptive behavior, so that students are more directed and responsible.